Hoe universeel zijn receptieve meertaligheidsstrategieën? Vreemde-taalleerders op school: een pilotstudie - Eva Knopp; Jentges, Sabin; Laurentzen, Chrissy; van Mulken, Margot (Dutch Journal of Applied Linguistics, 2021)
There are multiple ways in which language learners’ multilingual repertoire can be put to use in foreign language learning and teaching. One such use is receptive multilingualism (RM, cf. Blees & Ten Thije 2017). Despite the fact that RM has been found to be an effective means of communication between adult speakers of typologically related languages, like Dutch and German (see Beerkens, 2010; Van Mulken & Hendriks, 2015; Ribbert & Ten Thije, 2007), there is hardly any research investigating its use and effectiveness in younger learners in school settings (Ten Thije, Gulikers & Schoutsen, 2020). In this contribution, we present the results of a pilot study in which we investigate whether German secondary-school students make use of their multilingual repertoire by employing receptive multilingual strategies when decoding an unknown, but typologically related language (Dutch) and whether they can transfer these skills when decoding a less typologically related, unknown language (Maltese).